2017
DOI: 10.1111/ibi.12510
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian multinomial logistic exposure model for estimating probabilities of competing sources of nest failure

Abstract: Understanding causes of nest loss is critical for the management of endangered bird populations. Available methods for estimating nest loss probabilities to competing sources do not allow for random effects and covariation among sources, and there are few data simulation methods or goodness-of-fit (GOF) tests for such models. We developed a Bayesian multinomial extension of the widely used logistic exposure (LE) nest survival model which can incorporate multiple random effects and fixed-effect covariates for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
0
19
1
Order By: Relevance
“…We expanded the Bayesian DSR model to explicitly estimate cause-specific rates of nest failure so that we could test for seasonality in competing risks as well as DSR. We followed the conceptual approach of a risk-partitioning nest survival model previously developed in a maximum-likelihood framework (Etterson et al 2007), which has recently been demonstrated in a Bayesian framework that allows the inclusion of random effects (Darrah et al 2017). Our model differed from that of Darrah et al (2017) in that we used a DSR model rather than a logistic-exposure model.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…We expanded the Bayesian DSR model to explicitly estimate cause-specific rates of nest failure so that we could test for seasonality in competing risks as well as DSR. We followed the conceptual approach of a risk-partitioning nest survival model previously developed in a maximum-likelihood framework (Etterson et al 2007), which has recently been demonstrated in a Bayesian framework that allows the inclusion of random effects (Darrah et al 2017). Our model differed from that of Darrah et al (2017) in that we used a DSR model rather than a logistic-exposure model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We followed the conceptual approach of a risk-partitioning nest survival model previously developed in a maximum-likelihood framework (Etterson et al 2007), which has recently been demonstrated in a Bayesian framework that allows the inclusion of random effects (Darrah et al 2017). Our model differed from that of Darrah et al (2017) in that we used a DSR model rather than a logistic-exposure model. Unlike Etterson et al (2007) and Darrah et al (2017), we also assessed the probability of each risk as conditional on failure; that is, the survival process was evaluated first (whether the nest survived or failed), and for nests that failed, the probability of each cause of failure was then evaluated.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested the effect of fences, cameras, and ordinal date of nest visit on nest fates (species pooled) at Three Lakes (2015–2018) by constructing a Bayesian multinomial logistic exposure model (Darrah et al. ). This allows simultaneous modeling of multiple sources of nest failure using a unique set of covariates for each response level.…”
Section: Methodsmentioning
confidence: 99%
“…We used a Bayesian formulation of a logistic-exposure, multinomial nest mortality model to estimate daily survival for all nests, as well as daily probability of mortality from different predator types (Darrah et al 2018). We chose to present multinomial nest mortality rates because they can be compared across studies to infer larger scale patterns, which is a limitation of presenting only counts.…”
Section: Cause-specific Nest Mortality Analysismentioning
confidence: 99%